Revisiting the Paradigm Shift in Trauma Studies: Twenty-Five Years of Veena Das' 'Our Work to Cry: Your Work to Listen'. Issue 1 (June 2019) - Gupta, Arpita; Bhattacharya, Prama; Priya, Kumar Ravi
Abstract: While in the 1980s, Diagnostic and Statistical Manual (DSM) III created the diagnostic category of posttraumatic stress disorder (PTSD), social scientists like Veena Das were foregrounding the cultural or contextual processes that were shaping the intense distress of the survivors that the psychiatric model excluded in the study of disaster survivors. As widely held, Das' work on violence-hit humans, particularly, 'Our work to cry: Your work to listen', that is, a chapter in her book, Mirrors of Violence, remains one of the cornerstones in making social scientists realise the precedence to be given to the meanings and subjective experiences of trauma events from the perspective of the survivors. In this article, we attempt to highlight how this work of hers contributed to a paradigm shift in the field of trauma studies by illuminating: (a) the ways in which this shift entails focusing on the experiences of suffering shaped within the cultural and socio-political context, (b) the need to transcend the psychiatric model and (c) how ethnographic fieldwork enables the researcher to focus on the nuances of the everyday experiences of the trauma survivors.